REVERSE ENGINEERING ROTOR TURBIN ICEWIND TIPE CW - Hanseiba Parsaoran, (2020)
IceWind turbine is a wind turbine innovation developed by a startup company in Iceland called IceWind. This vertical axis wind turbine is claimed to be able to produce good performance at low wind speeds. But the problem is the ability of existing rotors is still possible to be developed further to get better performance. The study was conducted by modifying the existing types of Conventional IceWind Turbine Rotors. The study was conducted by testing the effect of the addition of end plate and the effect of the blade geometry shape on the Type CW IceWind Turbine Rotor. Design modeling is done using special 3D design software and for rotor simulation is done using flow simulation software. The test results show that the addition of end plates to the rotor can improve performance and several types of rotors with varying blade shapes produce different values of the power coefficient and torque coefficient based on the TSR range 0.1-0.8. With the addition of an end plate and proper blade design it is expected to improve rotor performance at low wind speeds.